Peri-Conception Folic Acid Knowledge Among Women in Reproductive Age Group Attending a Tertiary Care Centre - M S, Karunyaa; Priya, Prema; Jeyamani, B. (Journal of Neonatal Surgery, 2025)
Background:Peri-conceptional folic acid supplementation is a well-established preventive strategy for neural tube defects and other congenital anomalies. Despite public health recommendations, the awareness and utilization of folic acid among women of reproductive age in India remain inadequate. Objectives:To assess the knowledge, awareness, and utilization of peri-conceptional folic acid among women of reproductive age attending a tertiary care centre and to identify demographic predictors associated with awareness. Methods:A cross-sectional study was conducted among 400 women aged 18–45 years attending the outpatient clinics of a tertiary care hospital. Data were collected through a structured, pre-tested questionnaire capturing sociodemographic characteristics, knowledge regarding folic acid, and supplementation practices. Chi-square test was used to determine associations between demographic variables and folic acid awareness. Multivariate logistic regression analysis was performed to identify independent predictors of awareness. A p-value < 0.05 was considered statistically significant. Results:Out of 400 participants, 150 women (37.5%) were aware that folic acid prevents neural tube defects, and only 85 (21.3%) reported using folic acid before conception. Awareness was significantly associated with higher educational status (p < 0.001), employment (p = 0.002), and being primigravida (p < 0.001). Multivariate analysis revealed higher education (AOR = 2.84, 95% CI: 1.75–4.59, p < 0.001), primigravida status (AOR = 1.92, 95% CI: 1.12–3.29, p = 0.017), and employment (AOR = 1.68, 95% CI: 1.01–2.81, p = 0.046) as significant independent predictors of folic acid awareness. Conclusion:The study highlights suboptimal knowledge and usage of folic acid during the peri-conceptional period. Despite greater awareness among primigravida women, the overall preconceptional supplementation rate remains low. Strengthening antenatal education, especially targeting multigravida and undereducated women, is essential to bridge the knowledge-practice gap and improve maternal and fetal health outcomes.